2017
DOI: 10.1080/02656736.2017.1306120
|View full text |Cite
|
Sign up to set email alerts
|

Microwave ablation is effective against liver metastases from gastric adenocarcinoma

Abstract: MWA is a safe and useful alternative for liver metastases from gastric adenocarcinoma in selected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…In our study, the patients with 3-5 liver metastases had a median overall survival of 17 months, while those with 1-2 liver metastases had a median survival of 29 months (p ¼ .030). Zhou et al [40] published clinical results of microwave ablation in 32 patients with gastric adenocarcinoma liver metastasis and found that the number of liver metastases, therapeutic modalities and the presence of extrahepatic metastases were independent prognostic factors in a multivariate regression analysis. Multiple liver metastases were associated with poor biological behavior and treatment difficulty, ultimately influencing the patients overall survival [41].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the patients with 3-5 liver metastases had a median overall survival of 17 months, while those with 1-2 liver metastases had a median survival of 29 months (p ¼ .030). Zhou et al [40] published clinical results of microwave ablation in 32 patients with gastric adenocarcinoma liver metastasis and found that the number of liver metastases, therapeutic modalities and the presence of extrahepatic metastases were independent prognostic factors in a multivariate regression analysis. Multiple liver metastases were associated with poor biological behavior and treatment difficulty, ultimately influencing the patients overall survival [41].…”
Section: Discussionmentioning
confidence: 99%
“…However, 7 of these articles were case reports and 9 of them were non-gastric related liver metastases. We finally selected 12 eligible articles [911,1321] (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Pooled analysis of 4 [13,14,19,21] studies included 190 patients: 88 in RFA/MWA group and 102 in systemic chemotherapy group (Fig. 2B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main therapeutic methods are surgical resection, systemic chemotherapy, molecular targeted therapy, immunotherapy, and interventional therapy [ 1 , 14 , 16 ]. Simultaneous and heterogeneous liver metastases of gastric cancer can be treated by surgical resection or ablation, and both can respond to treatment [ 17 , 18 ]. There are some difficulties involved in the surgical treatment and ablation of multiple lesions and metastasis of special anatomical sites.…”
Section: Discussionmentioning
confidence: 99%